2018
DOI: 10.1111/bcp.13563
|View full text |Cite
|
Sign up to set email alerts
|

Large differences in neonatal drug use between NICUs are common practice: time for consensus?

Abstract: AimsEvidence for drug use in newborns is sparse, which may cause large differences in drug prescriptions. We aimed to investigate the differences between neonatal intensive care units (NICUs) in the Netherlands in currently prescribed drugs.MethodsThis multicentre study included neonates admitted during 12 months to four different NICUs. Drugs were classified in accordance with the Anatomical Therapeutic Chemical (ATC) classification system and assessed for on/off‐label status in relation to neonatal age. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 29 publications
5
33
2
Order By: Relevance
“…This was similar finding with that of study reports from Iran and Italy [3,24]. However, it was different from a study conducted in Netherlands which reported that blood products were the top class of medicines used in an off-label manner [20]. The difference might be related with difference in disease status.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This was similar finding with that of study reports from Iran and Italy [3,24]. However, it was different from a study conducted in Netherlands which reported that blood products were the top class of medicines used in an off-label manner [20]. The difference might be related with difference in disease status.…”
Section: Discussionsupporting
confidence: 81%
“…Accordingly, the overall off-label medicine use in ACSH NICU was found to be 67.58%. This was higher compared to several study findings elsewhere in the globe which reported off-label medicine use in the range of 23 to 62% [3,4,9,11,13,14,[20][21][22][23]. However, it was slightly lower compared to a study from India which reported an off-label prescription of 70% [2].…”
Section: Discussioncontrasting
confidence: 75%
“…Propofol is considered one of the acceptable options, despite being off-label for use in newborns, gaps in knowledge regarding optimal dosing and concerns about safety 12. Because of its rapid onset and recovery, and its ease of use, propofol as a sedative for endotracheal intubation has been implemented into clinical practice in several neonatal intensive care units (NICUs) 13–17. Previous trials studying propofol have shown conflicting results on sedative effect and concerning effects on blood pressure 16–19…”
Section: Introductionmentioning
confidence: 99%
“…The most comprehensive studies conducted in the United States based on national datasets showed that antibioticsampicillin and gentamicin were the most commonly used medicines [5,6]. European studies have covered single countries, single centers or only selected therapeutic groups like antibiotics [7,8]. Due to methodological variabilities between-country comparisons are complicated.…”
Section: Introductionmentioning
confidence: 99%